Understanding university professors' best mentoring practices in undergraduate research. Issue 1 (2nd January 2023) - Mohamad Nasri, Nurfaradilla; Nasri, Nurfarahin; Abd Talib, Mohamad Asyraf
ABSTRACT: Undergraduate research (UR) provides a sound academic foundation for student's personal and professional development. This study aims to provide understanding and investigate the best UR mentoring practices of university professors from various institutions and disciplines. A total of 20 semi-structured interviews were conducted and analysed using hybrid thematic analysis. Findings suggest common shared values on the importance of sharing personal research experience to build students' confidence and foster empathic mentoring skills. Moreover, tailoring mentoring pedagogies to meet the diverse students' learnings needs can be achieved by adapting the 'just in time' approach. This study further provides strategic recommendations to improve current UR mentorship programmes based on the emerging mentoring practices.